2022
DOI: 10.1159/000523910
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of circHIPK3-miRNA-124-3p/miRNA-148b-3p-Mediated Inflammatory Responses and Cell Senescence in <b><i>Candida albicans</i></b>-Induced Septic Acute Kidney Injury

Abstract: <b><i>Introduction:</i></b> Sepsis is a life-threatening inflammatory state that can result in septic acute kidney injury (SAKI). Circular RNAs (circRNAs) are implicated in various inflammatory diseases including SAKI. This study investigated the effect of circHIPK3 on inflammatory responses and cell senescence in <i>Candida albicans</i>-induced SAKI. <b><i>Methods:</i></b> circHIPK3 expression and inflammatory factors in the serum of SAKI patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…Existing evidence strongly suggests that depleting ROCK2 can effectively counteract TMZ resistance in glioma cells by disrupting the DNA repair system, a conclusion consistent with our study's findings. 12 Our results strongly indicate that increasing ROCK2 expression significantly enhances the susceptibility of glioma cells to TMZ, as demonstrated by a notable increase in the IC50 value of T98G cells for TMZ. Additionally, the lack of HUWE1 within cells may contribute to platinum resistance, potentially by enhancing DNA damage repair mechanisms and promoting resistance to apoptosis.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Existing evidence strongly suggests that depleting ROCK2 can effectively counteract TMZ resistance in glioma cells by disrupting the DNA repair system, a conclusion consistent with our study's findings. 12 Our results strongly indicate that increasing ROCK2 expression significantly enhances the susceptibility of glioma cells to TMZ, as demonstrated by a notable increase in the IC50 value of T98G cells for TMZ. Additionally, the lack of HUWE1 within cells may contribute to platinum resistance, potentially by enhancing DNA damage repair mechanisms and promoting resistance to apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…11 In glioma, ROCK2 is over-activated in TMZ-resistant glioma cells, and its suppression enhances glioma cell sensitivity to TMZ. 12 Strategies aiming to downregulate ROCK2 expression, such as using nanocomposites, have shown potential in sensitizing glioma cells to TMZ. 13 However, the precise molecular mechanism underlying the inhibitory effect of ROCK2 on chemoresistance in glioma cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fresh study recently showed that circXPO1 plays a key role in cigarette smoke‐induced inflammation and cellular senescence of alveolar epithelial cells in chronic obstructive pulmonary disease 94 . Moreover, circHIPK3 aggravated septic acute kidney injury (SAKI) inflammatory responses via miR‐124‐3p/KLF6 and accelerated SAKI cell senescence via miR‐148b‐3p/DNMT1/3a axis 95 …”
Section: Circular Rnas Regulate Cellular Senescence Via Various Pathwaysmentioning
confidence: 99%
“…Similar findings were noted for circ-HIPK3 in a murine model of AKI induced by Candida albicans , where the downregulation of circ-HIPK3 ameliorated the inflammatory response to sepsis, with reduced levels of IL-6 and TNF-α but increased levels of IL-10. This was likely due to the interaction of circ-HIPK3 with miR-124-3p and miR-148b-3p [ 33 ].…”
Section: Circrna Expression In Aki Due To Sepsismentioning
confidence: 99%